Nomophobia and Smartphone Usage Patterns among Medical Students at a Tertiary Care Medical College in Eastern Nepal - Acharya, Alok; Mishra, Rimu; Pokhrel, Ava; Niraula, Surya Raj; Shreewastav, Kritika (Journal of Nobel Medical College, 2026)
Background: Nomophobia, the fear of being without a mobile phone, is increasingly common among university students. Medical students may be particularly vulnerable due to their reliance on smartphones for academic and personal purposes. This study assessed the prevalence and associated factors of nomophobia among MBBS students. Materials and Methods: A cross-sectional study was conducted among 183 MBBS students selected through stratified random sampling. Data was collected using a structured questionnaire incorporating the Nomophobia Questionnaire (NMP-Q). Bivariate and multivariable logistic regression analyses were performed. Results: Mild, moderate, and severe nomophobia were observed in 47%, 40%, and 10% of participants, respectively. Students aged 21–26 years and those in higher academic years were more likely to have moderate-to-severe nomophobia. Participants used mobile phones during idle periods, particularly when bored (92.9%), alone (85.2%), or waiting for someone (80.9%). Large number of participants (61.2%) reported using phones immediately after waking up. Lower daily smartphone use (≤3 hours), fewer daily messages (≤20), and fewer installed applications (<25) were associated with lower odds of nomophobia. Conclusion: Nomophobia was highly prevalent among undergraduate medical students and was associated with age and academic year. Lower daily smartphone use, fewer daily messages, and fewer installed applications were inversely associated with nomophobia. Smartphone usage pattern was primarily communication- and study-oriented, with frequent use during idle moments, particularly when bored, alone, waiting, or immediately after waking.